EKOLINGUISTIK NILAI LOKAL DAN SPIRITUALITAS BAHASA DAYAK NGAJU: STRATEGI PELESTARIAN BUDAYA DI KALIMANTAN TENGAH - Ruliyani, Ruliyani; Windu Asrini, Hari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine the role of the Dayak Ngaju language in preserving ecological and spiritual values through key concepts such as handep (cooperation), hinting pali (traditional prohibitions), and sangiang (sacred spirits). This study uses an ecolinguistic approach to explore the relationship between language, ecology, and spirituality in the Dayak Ngaju culture. The method employed is literature review, collecting and analyzing 25 sources (including scholarly articles, books, and cultural documents). The literature selection process was carried out using the Google Scholar and JSTOR databases, with keywords